Notes on the genus Conanalus Tinkham, 1943 (Orthoptera: Tettigoniidae: Conocephalinae) with one new species from Yunnan, China - Du, Bao-Jie; Song, Qiong; Shi, Fu-Ming (Zootaxa, 2015)
The paper describes one new species, i.e. Conanalus bilobus sp. nov., and provides additional information on Conanalus brevicaudus Shi, Mao & Ou, 2008 (including female description for the first time), and Conanalus robustus Shi, Mao & Ou, 2008 from Yunnan, as well as illustrations of important morphological characters of Conanalus axinus Shi, Wang & Fu, 2005. A distribution map of the species of Conanalus from Yunnan, China is presented. The type material is deposited in the Museum of Hebei University.